Analisis Hukum terhadap Klaim Greenwashing Akuntabilitas Hukum di Era Branding Berkelanjutan - Raharjo, Budi; Kossay, Methodius (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Greenwashing poses significant challenges to sustainability initiatives in Indonesia, where weak regulatory frameworks and inconsistent enforcement exacerbate the issue. This study explores the interplay between greenwashing practices and legal regulations, aiming to identify gaps and propose solutions to address the problem. Employing a qualitative case study design, the research utilized document analysis, semi-structured interviews, and content observation to gather data from multiple stakeholders, including legal experts, industry practitioners, and consumer organizations. The findings reveal that 55% of sustainability claims in marketing materials lack verifiable evidence, highlighting transparency as a critical concern. Weak regulatory oversight and the absence of standardized definitions for terms like